SISTEM PAKAR DIAGNOSIS HAMA PADA TANAMAN MANGGA MENGGUNAKAN METODE ANALYTHICAL HIERARCHY PROCESS DAN CERTAINTY FACTOR - Septyaningtyas, Sasi; Novianti, Dian; Widhiani, Pahla (INTI TALAFA, 2025)
Mango is a major horticultural commodity in Indonesia with significant export potential, but pest attacks often hamper production. To address this problem, this study developed a web-based expert system using the Analytical Hierarchy Process (AHP) and Certainty Factor (CF) methods. AHP is used to prioritize pest control, while CF handles uncertainty in diagnosis based on the symptoms entered. The results show that the system can provide accurate diagnosis and appropriate control recommendations. The system’s accuracy is shown by its consistency with manual calculations, with only minor differences due to rounding. The system’s consistent rounding method ensures that these differences are insignificant, making the results as accurate and reliable as manual calculations. For example, the diagnosis of whitefly pests using manual calculation yields 41.03%, while the system yields a result of 41%, with the difference only in rounding. The application of this system is expected to help farmers identify pests more quickly and efficiently, thus maintaining mango production.